Hubungan Prokrastinasi, Budaya Ngaret dengan Agresivitas Berkendara di Wilayah Jabodetabek - Melodius Yusuf Hekmatyar; Johan Ramadhan Nurwardana (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The increasing number of motor vehicles, which has led to a rise in traffic congestion and accidents on the roads, has become a common phenomenon in major cities in Indonesia. This research aims to investigate the relationship between procrastination, known as